Life's hard and then you die: the end-of-life priorities of people experiencing homelessness in the UK. (2nd March 2020) - Webb, Wendy Ann; Mitchell, Theresa; Snelling, Paul; Nyatanga, Brian
Abstract : Background: People experiencing homelessness often die young and without adequate support. In the UK, they fail to access palliative care services and their end-of-life priorities remain poorly understood. Aims: To explore the end-of-life concerns, fears, preferences and priorities of a sample of people experiencing homelessness in the UK. Methods: This is an interpretive phenomenology. Data collected through semi-structured, audio-recorded, face-to-face interviews with 21 homeless participants in the UK were analysed iteratively using thematic analysis. Findings have been interpreted through the lens of Merleau-Ponty's philosophy. Results: Eight themes are reported: spiritual concerns; practical concerns; fear of needing care; fear of being forgotten; preference for dying suddenly; preference for being somewhere comfortable where people know me; prioritising autonomy and self-determination; and prioritising authenticity. Conclusion: A strengths-based, trauma-informed, person-centred, collaborative 'compassionate community' approach to care is recommended for people experiencing homelessness at end of life.